RNAseq, transcriptome analysis and identification of DEGs involved in development and ripening of Fragaria chiloensis fruit - Gaete-Eastman, Carlos; Stappung, Yazmina; Molinett, Sebastián; Urbina, Daniela; Moya-Leon, María Alejandra; Herrera, Raúl (Frontiers in Plant Science, 2022)
Fragaria chiloensis (Chilean strawberry) is a native species that produces fruit with an exotic pinkish color and a fruity aroma. It has a non-climacteric pattern of fruit ripening, and it is the mother of the commercial Fragaria x ananassa. The ripening of F. chiloensis fruit seems stimulated by ABA, and a complete set of genes participate in its softening, color, and aroma development. In addition, a set of transcription factors regulate the entire process, but few of them have been described. Over the last two decades, RNA-seq was used to identify genes at three fruit development/ripening stages, named C2 (unripe, large green) to C4 (full ripe), in whole fruit and fruit without achenes. A total of 204,754 contigs were assembled considering all samples, obtaining an N50 of 1.125 bp. Differentially expressed genes (DEGs) between two samples were identified, obtaining a total of 77,181 DEGs. Transcripts for genes involved in ABA biosynthesis present high and differential expression during the C2, C3, and C4 stages. Besides, contigs corresponding to ABA receptors, which interact with a regulatory network, are also differentially expressed. Genes associated with cell wall remodeling and those involved in flavonoid synthesis were also differentially expressed. An interaction network was built considering differentially expressed genes for the phenylpropanoid and flavonoid molecular pathways and having FcMYB1 as a transcription factor regulator. Identifying key genes could give an option to control the ripening of this non-climacteric fruit.